The effect of pegbovigrastim on circulating neutrophil count in dairy cattle: A randomized controlled trial. - Sabrina J Van Schyndel; Jérôme Carrier; Osvaldo Bogado Pascottini; Stephen J LeBlanc (PLoS ONE)
Previous research in various species has shown that granulocyte-colony stimulating factor stimulates the production and release of neutrophils from bone marrow. The objective of this study was to characterize the effects of polyethylene glycol-bound bovine granulocyte colony-stimulating factor (pegbovigrastim; Imrestor, Elanco) on circulating leukocyte counts. Thirty-four Holstein cows were randomly assigned to receive 2 injections of either physiologic saline (n = 16) or pegbovigrastim (n = 18), 7 days before expected calving (d -7) and within 24 hours after calving (d 0). Cows were sampled at d -7, d -6, d 0, d +1, d +7, and d +21, relative to calving. Only cows for which the interval from the first injection to calving was ≥ 4 d and ≤ 10 d were included, such that the interval (mean ± SD) from first treatment to calving was 6.7 ± 1.9 d. Treatment effects were assessed with mixed linear regression models. After the first injection, neutrophil counts (×109/ L) in pegbovigrastim-treated cows increased from 4.3 (95% CI 3.8 to 4.8) at d -7 to 18.2 (CI 16.3 to 20.3) at d -6 (P < 0.0001). Their counts then decreased from d -6 to d 0, when the second injection was administered, at a rate of -0.31 ×109 neutrophils/L/day (P < 0.0001). After the second injection, neutrophil counts increased from 16.4 (CI 13.7 to 19.6) at d 0 to 32.8 (CI 25.2 to 42.7) at d +1 (P < 0.0001), after which counts decreased at a rate of -3.73 ×109 neutrophils/L/day until d +7 (P < 0.0001). Counts continued to decrease from d +7 to d +21 at a slower rate of -0.43 ×109 neutrophils/L/day (P < 0.0001), until baseline levels were reached. Conversely, in control cows, neutrophil counts were unchanged from d -7 to d -6 (P = 0.86) after the first injection and then decreased from 6.1 (CI 5.0-7.3) at d 0, to 3.2 (CI 2.4-4.2) at d +1 (P < 0.0001) after the second injection. Neutrophil count was greater (P < 0.001) in pegbovigrastim-treated than in control cows at days -6, 0, +1 and +7. Area under the curve (cells ×109/ L per 28 d) for neutrophil counts in the pegbovigrastim group was 429, versus 99 in the control group (P < 0.0001). The response to each injection of pegbovigrastim was additive and consisted of 95% segmented neutrophils, suggesting that the effect of the treatment was to release mature neutrophils from a substantial pool available in the bone marrow. The sustained increase in circulating neutrophil count around the time of calving may contribute to improved health during the peripartum transition period.